Medical dictionary MedDRA: Used in over 60 countries, among which is Montenegro - Mugoša Snežana S.; Stanković Maja V.; Turković Nemanja M.; Šahman-Zaimović Majda M. (Srpsko lekarsko drustvo, 2015)
Introduction: Medical Dictionary for Regulatory Activities (MedDRA) is a medical coding dictionary which is designed in order to be used by regulatory authorities, pharmaceutical companies, clinical research organizations and health care professionals, i.e. all participants in the system of medicines safety monitoring. Methods: This article describes process which is used for medical coding in clinical data management and, in brief, most commonly used medical dictionary MedDRA. The purpose of this paper is a modest contribution to easier and more successful understanding of the encoding process in clinical data management in the field of pharmacovigilance. Topic: MedDRA Development, structure, multi-axiality, availability of foreign languages, as well as common problems faced by medical coding expert while coding were presented. Conclusion: MedDRA has become the standard medical terminology for drug regulators and pharmaceutical companies in Montenegro. Training should be provided to all coders in order to achieve the optimum level of coding and to ensure that all the parameters for quality are achieved. Coding should be treated as one of the most important function in clinical research.